Improving Floor Exercise Learning Outcomes through the Problem Based Learning Model for Class VI Students - Ansyarullah, M. Rajib; Fauzan, Lazuardy Akbar; Suadmaji, Suadmaji (Empiricism Journal, 2026)
The low achievement of students in floor exercise learning was identified as a major problem in Class VI A at State Elementary School 1 Landasan Ulin Selatan. Previous studies have reported positive effects of Problem Based Learning (PBL) in Physical Education; however, limited evidence has explained how PBL can be adapted to elementary-school floor exercise learning that requires balance, flexibility, confidence, and peer-supported correction. This study aimed to improve students’ learning outcomes in floor exercise through the implementation of a PBL-based classroom action strategy.This study employed Classroom Action Research (CAR) consisting of two cycles, with each cycle involving planning, action, observation, and reflection stages. The participants were 22 sixth-grade students enrolled in the second semester of the 2025/2026 academic year. Participants were selected purposively based on preliminary observations indicating low learning outcomes in floor exercise. Data were collected through performance tests, observation sheets, and documentation. The instruments were reviewed by experts prior to implementation, and the collected data were analyzed using descriptive quantitative and qualitative techniques.The findings showed continuous improvement across the research cycles. Learning mastery increased from 22.73% in the pre-cycle stage to 63.64% in Cycle I and reached 86.36% in Cycle II. Similarly, the class average score improved from 52.3 to 68.4 and further increased to 81.2. Improvements were also observed in the cognitive, psychomotor, and affective domains, indicating positive development in students’ understanding, movement performance, participation, cooperation, and confidence.The findings suggest that a structured learning approach integrating Problem Based Learning, collaborative practice, peer correction, drill activities, repeated movement practice, and teacher guidance may support improved floor exercise learning outcomes among elementary-school students. However, the results are limited to a single classroom context and should be interpreted cautiously.